Anthranils: versatile building blocks in the construction of C–N bonds and N-heterocycles. Issue 9 (16th April 2020) - Gao, Yang; Nie, Jianhong; Huo, Yanping; Hu, Xiao-Qiang
Abstract : This review article provides an overview of the recent progress in the transformations of anthranils, which have emerged as versatile building blocks in the assembly of various C–N bonds and medicinally active heterocyclic systems. Abstract : Anthranils are readily available and have recently emerged as versatile building blocks in the assembly of various C–N bonds and medicinally active heterocyclic systems. A great variety of amination reactions, including cross-coupling reactions, C–H aminations and annulation reactions, have been intensively developed with the use of anthranils as aminating synthons. The success of these impressive reactions demonstrates the great synthetic potential of anthranils, which provides a powerful platform for C–N bond formation and heterocycle synthesis. In this review, we mainly summarize the recent progress in the representative transformations of anthranils with special emphasis on mechanistic aspects. We hope that a deep understanding of the unique properties of anthranils and the underlying working mechanism can provide a guideline for researchers who are interested in anthranil chemistry, leading to further exploration of novel and efficient catalytic systems for C–N bond construction.